Terahertz dual-band antenna design with improved performances using FSS-based metasurface concept for wireless applications - Youssef Amraoui; Imane Halkhams; Rachid El Alami; Mohammed Ouazzani Jamil; Hassan Qjidaa (Scientific African)
The suggested design makes use of the concept of a metasurface by including a Frequency Selective Surface (FSS) underneath the radiating element. This research paper aims to present the design and performance analysis of FSS embedded antennas with a special focus on the terahertz frequency band. The work reviews the electromagnetic theory of FSS structures and identifies some of the most important design parameters including the unit cell size and the choice of materials that define the performance of the antenna. Employing simulation software including CST, HFSS and ADS, the research output demonstrates the effects of FSS on the gain and efficiency of antenna systems. it is composed of a square loop metallic element with modified cross-shaped structures with a relative permittivity of 11.9 are positioned on a silicon dioxide substrate. To further boost the antenna's peak gain, the FSS is added 82 µm below the current THz antenna. The FSS construction has a total volume of 550 × 850 µm2. By appropriately integrating the FSS with the antenna construction and making use of its frequency-selective properties, gain enhancement can be achieved. Furthermore, circuit theory techniques have been used to study FSS structure and electrical equivalent circuits have been created to confirm their functionality. The intended frequency of operation for the FSS is 0.7 THz. The FSS antenna exhibits radiation efficiency of 85.59 % and 87.75 % at resonance frequencies of 600 GHz and 700 GHz, respectively. When we utilize FSS, the gain improves from 7.14 dBi to 8.36 dBi at 600 GHz and from 5.69 dBi to 6.79 dBi at 700 GHz. The smaller size of the dual-band structure adds to the compactness of the design, which can benefit applications requiring high-performance, dual-band operation. This demonstrates the advantages of FSS based solutions for advanced antenna systems in modern communication systems.